THE INVISIBLE EFFECTS OF CONFLICTS ON MSAJED, AND THERE SOLUTIONS ACCORDING TO ISLAMIC LAWS (SHARI'A)- (Islamic Sciences Journal, 2023)
Conflicts swept the earth and Iraq had a big share of there effects.      Some of these effects that were visible had many solutions and  took a great deal of care ,but a lot of effects were not visible and they are  hardly getting any care not even a little and so came the research in the field of "the invisible effects of conflicts on msajed", because of the subjects great importance. We tried to investigate the most important of these effects and we explained  the practiced islamic law, and if there was a disput we tried to solve the issue according to the purposes of the islamic law in a way not opposing the islamic law constants.